2017
DOI: 10.1111/pbi.12741
|View full text |Cite
|
Sign up to set email alerts
|

Molecular engineering and plant expression of an immunoglobulin heavy chain scaffold for delivery of a dengue vaccine candidate

Abstract: SummaryIn order to enhance vaccine uptake by the immune cells in vivo, molecular engineering approach was employed to construct a polymeric immunoglobulin G scaffold (PIGS) that incorporates multiple copies of an antigen and targets the Fc gamma receptors on antigen‐presenting cells. These self‐adjuvanting immunogens were tested in the context of dengue infection, for which there is currently no globally licensed vaccine yet. Thus, the consensus domain III sequence (cEDIII) of dengue glycoprotein E was incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 48 publications
5
50
0
2
Order By: Relevance
“…(a) Schematic representation of the monomeric and polymeric human IgG1‐ cEDIII fusion protein and its interaction with high and low‐affinity Fc gamma receptors on antigen‐presenting cells; further details of the structure of these molecules are described in Kim et al . (). Red represents cEDIII domain, while dark and light blue indicate CH 2 and CH 3 domains of human IgG1, respectively.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…(a) Schematic representation of the monomeric and polymeric human IgG1‐ cEDIII fusion protein and its interaction with high and low‐affinity Fc gamma receptors on antigen‐presenting cells; further details of the structure of these molecules are described in Kim et al . (). Red represents cEDIII domain, while dark and light blue indicate CH 2 and CH 3 domains of human IgG1, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…We describe a novel vaccination approach against dengue infection based on Fc-antigen fusion approach. We previously expressed D-PIGS molecules based on murine IgG2a and showed that they were highly immunogenic in mice (Kim et al, 2017). To translate this promising vaccine approach into a potential dengue vaccine candidate in humans, we generated the human version of D-PIGS and purified them to a high degree of homogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations